PALLIATIVE CARE RESILIENCE: ADVERSITY QUOTIENT AMONG CANCER PATIENTS IN NAIROBI AND NYERI COUNTIES, KENYA - Wang'ombe, Joyce; Kathungu, Beatrice (Journal of Advanced Psychology, 2021)
Purpose: This study sought to find out the levels of Adversity Quotient among cancer patients attending palliative care in Nairobi and Nyeri Counties, Kenya. Methodology: The study adopted a correlation research design. The target population were the cancer patients, attending treatment at the three palliative care units in Nairobi and Nyeri Counties. Systematic random sampling technique was used in the study to obtain a sample of 96 participants. Semi structured questionnaires were used to collect data. Data was analysed using both descriptive and inferential statistics, namely Pearson Moment Correlation Coefficient(r). Findings: Results showed that the lowest adversity quotient level score attained by the respondents was 32, while the highest score was 93. The adversity quotients mean score was 68.98+13.54, signifying that the adversity quotient for the respondents was in the moderate level possibly because majority of them had been diagnosed with cancer between 1 to 2 years earlier hence may have still been overwhelmed by their illnesses and the subsequent cost in initiation of treatment and diet thus lowering their AQ to moderate levels. Unique contribution to theory, practice and policy: Patients under palliative care could adopt group psychotherapy, including cognitive-behavioural, informational, non-behavioral, social support, and using unusual treatments such as music and art therapy to curb cancer. More cancer related programs enhancing patients AQ should be put in place by the counsellors in order to increase the patients AQ in the palliative care units from moderate level to high level of AQ in order to boost recovery outcomes